"Water-in-Salt" electrolytes enable green and safe Li-ion batteries for large scale electric energy storage applications. Issue 17 (19th April 2016) - Suo, Liumin; Han, Fudong; Fan, Xiulin; Liu, Huili; Xu, Kang; Wang, Chunsheng
Abstract : A new, safe, green and economical aqueous Li-ion chemistry based on LiFePO4 /water-in-salt/Mo6 S8 was designed targetedly for large-scale energy electric storage (EES) applications. Abstract : Although state-of-the-art Li-ion batteries have overwhelmed the market of portable electronics as the main power source, their intrinsic limitations imposed by concerns over their safety, toxicity and cost have prevented them from being readily adopted by large-scale electric energy storage applications. Leveraging the new class of aqueous electrolytes of wide electrochemical stability window to resolve these concerns, we describe a new aqueous Li-ion chemistry based on LiFePO4 /water-in-salt/Mo6 S8 that is safe, green and economical. These merits, along with superior electrochemical performances such as excellent cycling stability (>1000 cycles), both high coulombic and round-trip efficiencies, high rate capability, low self-discharge rate at the fully charged state, as well as a wide service temperature range (−20 to +55 °C), make this new battery chemistry a promising candidate in energy storage units for large-scale applications.